Electrochemical sensors of neonicotinoid insecticides residues in food samples: From structure to analysis - Zhang, Changqiu; Li, Yanqing; Yang, Ningxia; You, Minghui; Hao, Jinhua; Wang, Jiacheng; Li, Juxiu; Zhang, Min (Talanta (Oxford), 2024)
Most food samples are detected positive for neonicotinoid insecticides, posing a severe threat to human health. Electrochemical sensors have been proven effective for monitoring the residues to guarantee food safety, but there needs to be more review to conclude the development status comprehensively. On the other hand, various modified materials were emphasized to improve the performance of electrochemical sensors in relevant reviews, rather than the reasons why they were selected. Therefore, this paper reviewed the electrochemical sensors of neonicotinoid insecticides according to bases and strategies. The fundamental basis is the molecular structure of neonicotinoid insecticides, which was disassembled into four functional groups: nitro group, saturated nitrogen ring system, aromatic heterocycle and chlorine substituent. Their relationships were established with strategies including direct sensing, enzyme sensors, aptasensors, immunosensors, and sample pretreatment, respectively. It is hoped to provide a reference for the effective design of electrochemical sensors for small molecule compounds. [Display omitted] •Four functional groups of neonicotinoids are basis for their electrochemical sensors.•Electro-active of nitro group is beneficial for direct sensing.•Saturated nitrogen ring systems results in the absence of enzyme sensors.•Aromatic heterocyclics and saturated nitrogen ring systems are vital in aptasensors recognition.•Chlorine substituent is crucial to synthesize antibodies applied in immunosensors.